U.S. fast burst reactors : design and operational history - Schmidt, Theodore R., 1938- (American Nuclear Society, 2017)
"This book describes the comprehensive work associated with U.S. fast burst reactors (FBRs). It includes historical backgrounds and technical descriptions of all 13 FBRs that were operated. It summarizes the wealth of information developed in the design and operation of FBRs and recognizes and preserves the enormous contribution of FBRs to scientific knowledge"--